Application of botulinum toxin in the treatment of bruxism - Małgorzata Milanowska; Paulina Dudzińska; Aleksandra Grudzińska; Dominika Jarosz; Hanna Tsitko (Kazimierz Wielki University, 2022)
Bruxism is a commonly reported functional para-function of the oral cavity. Its symptoms are quite characteristic and include, above all, excessive clenching and grinding of the teeth. (2) Other complaints most frequently reported by patients are headaches, pain in the temporomandibular joint, excessive tooth abrasion, damage to dentures, waking up at night, visual effect - the so-called "square jaw". The etiology is multifactorial therefore it is difficult to treat its symptoms.  Botulinum toxin is a neurotoxin produced by the anaerobic bacteria Clostridium botulinum. Its mechanism is based on the reversible inhibition of acetylcholine release in neuromuscular junctions. Intramuscular injection of botulinum toxin is one of the treatments of bruxism. So far, this method is used off-label. Looking at the promising results of randomized studies on the use of botulinum toxin in bruxism, this may change in the near future. As shown by previous studies, it is not an ideal method, but nevertheless it is one of the most effective and the best for the patient. The downside to the use of botulinum toxin in the treatment of bruxism symptoms are, inter alia, contraindications to the use of this drug and the duration of its action - 3-6 months. This systematic review of selected articles and studies aims to examine the available literature in order to determine the effectiveness of the use of botulinum toxin in the treatment of bruxism and to assess whether it is currently the most effective method.  Pubmed and Google Scholar were searched for literature.